Standardization of Pre-Sowing Treatments with Panchagavya, Beejamrutha, Jeevamrutha, and Neem Oil for Growth, Yield, and Yield Attributing Traits of Cowpea (Vigna unguiculata L.) - VISHNUVARDHAN CH,; PRASHANT KUMAR RAI, (Seed Research, 2026)
Cowpea (Vigna unguiculata L.), a crucial legume for both nutrition and soil enrichment, stands to gain from effective organic treatments. This study investigated the impact of Panchagavya, Beejamruth, and Jeevamruth on Cowpea variety Pusa Phalguni, conducted during the Rabi season of 2021 at Sam Higginbottom University, Prayagraj. Seeds were treated with these organic formulations, and key growth and yield parameters, including field emergence, plant height, flowering and maturity times, number of branches, pods per plant, pod length, seeds per pod, seed index, seed yield, biological yield, and harvest index were meticulously assessed. Panchagavya at 7% and Beejamrutha 5% emerged as the most effective treatment, significantly outperforming other treatments and the control in enhancing plant growth and yield. This research underscores Panchagavya and Beejamrutha as a transformative organic solution, offering a compelling advantage for boosting Cowpea productivity and supporting sustainable agricultural practices.